IMPLEMENTATION OF CUSTOMER RELATIONSHIP MANAGEMENT IN THE GALLERY SAHABAT MUSLIMAH - Yunita Sari; Riki Andri Yusda; Andri Nata (Informatika, Universitas Jenderal Soedirman, 2022)
Gallery Sahabat Muslimah is a business engaged in selling Muslim clothing or fashion needs such as robes, skirts, headscarves, socks, masks and others. Gallery Sahabat Muslimah currently does not have its own website to market the products it sells. In addition, orders are still made by recording manually so it is inconvenient if there are customers who cancel their orders. Currently, the Friends of Muslimah Gallery market its products offline and online using the FACEBOOK application media which is still an obstacle because the menu display regarding the product is not available in full, such as existing stock, ordering, promotion, and payment methods. So it is necessary to have a Customer Relationship Management system that is made in the form of a web-based system that will help to increase sales and customer loyalty because it has been computerized. This system was created to make it easier for customers to make purchases or order products, view the latest items, view product stock, view promotions and be able to make payments online or via bank and others.